Current distribution in grounding grid conductors with and without vertical rods buried in two‐layer soil model. Issue 9 (4th June 2018) - Gouda, Osama E.; Dessouky, Sobhy S.; Kalas, Ahmed E.; Hamdy, Mohamed A.
Abstract : For the safe and reliable operation of an electrical system, grounding grids are used. The current distribution in such grounding grid conductors is calculated by either an analytical or a numerical method. This paper presents a new method to obtain the current distribution in grounding grid conductors with and without vertical rods buried in two layers of soil. The two‐layer soil model has been simulated mathematically using two suitable values of resistivity. The computations of the current distribution have been based on the current for each segment of meshes. The investigation includes different meshes, such as one mesh, four meshes, nine meshes, and/or also more meshes. The calculation technique of current distribution is carried out to give all the mutual resistances with respect to ( x, y, z ) coordinates of each segment to solve the equation containing all segment currents of the meshes. The results in this paper give the current distribution for each segment of each mesh with and without the driving rods. The effect of vertical rods, which are connected to the horizontal grounding grid, on the current distribution and grounding resistance for different grounding grid dimensions and shapes has been studied. For increasing the flexibility of current distribution calculations of the grounding grids, the per‐unit system has been used in this paper. An experimental model to simulate the two‐layer soil model is presented for the validation of the calculated results. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.